2021
DOI: 10.1111/jfpe.13786
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of paneer prepared by automated pressing technique

Abstract: In this study, paneer was prepared by conventional method as well as by employing an automated pressing equipment and microstructure of paneer samples was studied by scanning electron microscopy. Further, pneumatic pressing of the hot coagulum was carried out at different pressures (2.5, 3.0, and 3.5 kg cm−2) and time durations (10, 12.5, and 15 min) using a semi‐automated microprocessor based pneumatic pressing unit. It was found that the microstructure of paneer comprised mainly of continuous medium of casei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Micrographs of Paneer (Figure 8) revealed that Paneer is basically a continuous dense cluster of the protein matrix of casein particles forming interconnected chains with numerous intergranular diverse sized spaces within which the liquid phase is immobilized which is in agreement with Sinha et al (2021); where fat globules remain embedded in the network while the water or whey got entrapped in capillaries as well as in the void spaces.…”
Section: Resultssupporting
confidence: 86%
“…Micrographs of Paneer (Figure 8) revealed that Paneer is basically a continuous dense cluster of the protein matrix of casein particles forming interconnected chains with numerous intergranular diverse sized spaces within which the liquid phase is immobilized which is in agreement with Sinha et al (2021); where fat globules remain embedded in the network while the water or whey got entrapped in capillaries as well as in the void spaces.…”
Section: Resultssupporting
confidence: 86%
“…Sinha et al . (2021) also reported that there was significant effect of pressure and time on chewiness of Paneer .…”
Section: Resultsmentioning
confidence: 91%
“…The chewiness for product in circular, square and rectangular test cell ranged from 5.87 to 18.90 N, 6.59 to 22.11 N and 6.95 to 22.44 N. The effect of test cell, pressure and time were found to be significant (P-value <0.05). Sinha et al (2021) also reported that there was significant effect of pressure and time on chewiness of Paneer.…”
Section: Effect Of Shape Of Test Cell Pressure and Time On Other Text...mentioning
confidence: 92%